2023
DOI: 10.1029/2022jd037758
|View full text |Cite
|
Sign up to set email alerts
|

Fire Influence on Regional to Global Environments and Air Quality (FIREX‐AQ)

Abstract: The NOAA/NASA Fire Influence on Regional to Global Environments and Air Quality (FIREX-AQ) experiment was a multi-agency, inter-disciplinary research effort to: (a) obtain detailed measurements of trace gas and aerosol emissions from wildfires and prescribed fires using aircraft, satellites and ground-based instruments, (b) make extensive suborbital remote sensing measurements of fire dynamics, (c) assess local, regional, and global modeling of fires, and (d) strengthen connections to observables on the ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 286 publications
(253 reference statements)
2
39
0
Order By: Relevance
“…Here we present results from the FIREX-AQ field study where we conducted airborne thermal denuder measurements that quantified the volatility of bulk BBPM and BBOA as well as the volatility of key molecular components of BBPM such as levoglucosan and nitrocatechol. These measurements are the first of their kind and serve to constrain the volatility of BBPM.…”
Section: Introductionmentioning
confidence: 99%
“…Here we present results from the FIREX-AQ field study where we conducted airborne thermal denuder measurements that quantified the volatility of bulk BBPM and BBOA as well as the volatility of key molecular components of BBPM such as levoglucosan and nitrocatechol. These measurements are the first of their kind and serve to constrain the volatility of BBPM.…”
Section: Introductionmentioning
confidence: 99%
“…To relate in situ aircraft emissions to GOES FRP at the fire source, the time of emission is calculated from the smoke age. Smoke age is determined as the time elapsed from smoke production until measurement by the aircraft and is estimated from average wind speed and distance from the fire source or using trajectory models that implement high-resolution meteorological datasets and an assumed vertical transport. , The time of emission is estimated as the time of sampling minus the calculated smoke age. The average FRP across each plume transect emission window was estimated and then averaged together with additional transects to estimate a fire-averaged FRP for selected emission windows.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we build upon the work described by Sekimoto et al . on laboratory fires and parameterize the VOC emissions from real-world wildfires using VOC measurements from the NOAA PTR-ToF-MS conducted on board the NASA DC-8 during the 2019 FIREX-AQ campaign (Fire Influence on Regional and Global Environments and Air Quality) . We conduct a constrained PMF analysis and show that the high- and low-temperature pyrolysis factors obtained in the FireLab 2016 experiment describe the variability of many VOCs emitted from western US wildfires, independent of fuel type.…”
Section: Introductionmentioning
confidence: 99%
“…The major FIREX‐AQ eastern fuel types and their definitions are given below, and these can be found in detail in Warneke et al. (2023) and Schwarz and Fuel2Fire Team (2023).…”
Section: Description Of Crop Residue and Prescribed Fire Plumes Sampl...mentioning
confidence: 99%
“…A goal of FIREX-AQ was to expand EF availability and statistics for crop residue and prescribed fires (Warneke et al, 2023). This need was emphasized by Akagi et al (2011) and demonstrated by differences in crop residue fire EFs between the 15 crop residue fires sampled in the Southeast US by Liu et al (2016) and the earlier global compilation of Akagi et al (2011) that is commonly used in models and fire emission inventories.…”
Section: Comparison With Prior Global Compilations and Regional Studiesmentioning
confidence: 99%